High-performance diesel biodegradation using biogas digestate as microbial inoculum in lab-scale solid supported bioreactors - Olivera, Camila (2024)
Fil: Olivera, Camila. Pontificia Universidad Católica Argentina. Facultad de Química e Ingeniería del Rosario; Argentina